Factors associated with the permission for child vaccination in the context of the COVID-19 pandemic - Diane Fernandes dos Santos; Jayane Omena de Oliveira; Ana Carolina Santana Vieira; Regina Célia Sales Santos; Alanna Michella Oliveira de Albuquerque da Silva; Christefany Régia Braz Costa (Revista Gaúcha de Enfermagem, 2023)
ABSTRACT Objective: To identify factors associated with permission for child vaccination in the context of the COVID-19 pandemic. Method: Cross-sectional study, with parents/guardians of children aged up to 1 year, 11 months and 29 days, aged 18 years or older, with internet access and residents of the state of Alagoas. The collection was conducted between June 2021 and April 2022, using a structured instrument via Google forms®. Fisher’s Exact and Pearson’s chi-square statistical tests were used. Results: A total of 94 parents/guardians participated. There was an association between permission for child vaccination during the COVID-19 pandemic and higher education level of parents/guardians, with the lack of an educational bond with the child, and between parents/guardians who would allow the application of the COVID-19 vaccine. Conclusion: Permission for child vaccination in the context of the COVID-19 pandemic was associated with higher education level of parents/guardians and the absence of educational bond of the child.